Tingkat Pengetahuan dan Perilaku Pencegahan Coronavirus Disease 2019 (COVID-19) Pada Masyarakat Sulawesi Utara: Level of Knowledge and Preventive Behavior towards Coronavirus Disease 2019 (COVID-19) in the Community of North Sulawesi - Lenny Gannika; Erika Emnina Sembiring (NERS Jurnal Keperawatan, 2020)
The Coronavirus Disease (COVID-19) pandemic that happens world widely including Indonesia have caused new habits to emerge in the society. The number of confirmed positive cases increased without seeing someone’s background includes it’s educational background makes the society have to be aware about the importance of COVID-19 prevention behavior. The goal is to know the correlation between level of education and COVID-19 prevention behavior of the people in North Sulawesi. This study uses quantitative research with cross sectional approach and with the total sample 390 respondents. This research was delivered by filling the online questionnaire that can be access through https://bit.ly/3gOVe5h. The data analyzed by using pearson chi square test. The result shows the value of p=0,000 <0.05 which means there is a correlation between level of education and COVID-19 prevention behavior of the people in North Sulawesi. The higher the level of education of someone hence the better the COVID-19 prevention behavior.